2009
DOI: 10.1021/tx9004192
|View full text |Cite
|
Sign up to set email alerts
|

New Urinary Metabolites Formed from Ring-Oxidized Metabolic Intermediates of Styrene

Abstract: The urine from mice exposed to styrene vapors (600 and 1200 mg/m(3), 6 h) was analyzed for ring-oxidized metabolites of styrene. To facilitate the identification of metabolites in urine, the following potential metabolites were prepared: 2-, 3-, and 4-vinylphenol (2-, 3-, and 4-VP), 4-vinylpyrocatechol, and 2-, 3-, and 4-vinylphenylmercapturic acid (2-, 3-, and 4-VPMA). For the analysis of vinylphenols beta-glucuronidase-treated urine was extracted and derivatized with acetanhydride/triethylamine before inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The ratios for the different TMA isomers (2/1/6: o/m/p) are similar to those found for the corresponding ring oxidation mercapturic acids of ethylbenzene in rat (1/2/6) (Cossec et al, 2010) and for styrene in mice (2/1/6) (Linhart et al, 2010). Thus, the rates for glutathione's reaction with the 2,3-oxide and 3,4-oxide appear to be the same for all monosubstituted aromatic compounds in rodents.…”
Section: Discussionsupporting
confidence: 80%
“…The ratios for the different TMA isomers (2/1/6: o/m/p) are similar to those found for the corresponding ring oxidation mercapturic acids of ethylbenzene in rat (1/2/6) (Cossec et al, 2010) and for styrene in mice (2/1/6) (Linhart et al, 2010). Thus, the rates for glutathione's reaction with the 2,3-oxide and 3,4-oxide appear to be the same for all monosubstituted aromatic compounds in rodents.…”
Section: Discussionsupporting
confidence: 80%
“…Not only does it indicate that the protein modification attributed to the conjugation of styrene oxide with cysteine residues, but also it tells us that the antibody binding resulted from immunochemical recognition and not from non-specific binding. Recently, Linhart and co-workers reported urinary aromatic mercapturic acids in mice given styrene, indicating the formation of arene oxides as metabolic intermediates [52]. We may not exclude possible involvement of the reported arene oxides in protein adduction.…”
Section: Discussionmentioning
confidence: 87%
“…The ratio of the detected 2-VP, 3-VP, and 4-VP was 27.7:1.0:2.8 in mouse liver microsomes. In a recent study, Linhart et al (2010) reported the detection of urinary 3-VP, 4-VP, possible 2-VP, and mercapturic acids derived from styrene-3,4-oxide and styrene-2,3-oxide in mice given styrene. They found approxi- mately 3-fold more mercapturic acid derived from styrene-3,4-oxide than that derived from styrene-2,3-oxide in the urine, inferring that styrene-3,4-oxide dominated in the formation of styrene arene oxides.…”
Section: Discussionmentioning
confidence: 99%
“…2-Vinylphenol (2-VP) and 3-vinylphenol (3-VP) have been proposed as aromatic hydroxylation products of styrene (Sumner and Fennell, 1994), but they have never been identified either in experimental animals or in humans exposed to styrene. Most recently, Linhart et al (2010) reported urinary 3-VP, 4-VP, and possible 2-VP in mice exposed to airborne styrene. Cruzan et al (2009) stated that differences in styrene oxide blood concentrations did not account for the species selectivity and tumor response to styrene.…”
Section: Introductionmentioning
confidence: 99%